Motif Berprestasi dengan Komitmen Organisasi pada Guru Honorer di Sekolah Swasta - Norhasanah, Norhasanah; Mulyani, Mulyani; Komalasari, Shanty (Islamic Psychology Study Program, Faculty of Ushluddin and Humanities, UIN Antasari Banj, 2020)
The purpose of this study was to determine the relationship of achievement motives with organizational commitment to honorary teachers in private schools. The population in this study was honorary teachers of private schools, especially in the 4 schools, which amounted to 12 non-permanent employees. Sampling uses a quota sampling because the number of subjects is less than 30 subjects. The data in this study are quantitative data, data collection in this study is to use the questionnaire method in the form of scales, interviews, and documentation. The research data were analyzed using linear regression analysis. The results showed that there was no relationship between achievement motives and organizational commitment. The results of the calculation of correlation using the Spearman rank correlation coefficient test can be seen the value of Sig. (2-tailed) is 0,112. Meanwhile, the correlation coefficient value of 0,482 means that the strength of the correlation coefficient between the achievement motive variable and organizational commitment is sufficient. The percentage of effective contribution of achievement motivation influencing organizational commitment is only 1,82% and 98,18% is influenced by variables or other factors not covered in this study.